Practical training report air conditioning system service at head office Perbadanan Putrajaya (PPJ) / Fatin Nadzirah Abd Rahim - Abd Rahim, Fatin Nadzirah (2017)
Perbadanan Putrajaya / Putrajaya Corporation (PPJ) was established under the Perbadanan Putrajaya 1995 (Act 536) for the purpose of managing and administering the Federal Territory of Putrajaya. Perbadanan Putrajaya (PPJ) or Putrajaya Corporation (PJC) is a local authority which administrates the Federal Territory of Putrajaya. This agency is regulated under Federal Territories Ministry of Malaysia. Perbadanan Putrajaya was originally established as a unit which is coordinated by the Prime Minister called Putrajaya Federal Government Development Unit in April 1995.This unit was established with the aim of designing, developing, administering and managing the Federal Territory of Putrajaya on behalf of the Federal Government. It is chaired by the Deputy Secretary General of the Prime Minister, assisted by a director and eight employees.